Quem manda no futebol da Paraíba? : elites políticas e estado novo (1941-1947) - Leite, Diogo Pimenta Pereira (2017)
The present work seeks to investigate aspects of football life in Paraíba from the formation of their leagues, specifically the Federação Desportiva Paraibana throughout its existence from 1941 to 1947. Founded by the decree law n.3.199 hat regularized the sports and professionalised the Soccer in the country, under the tutelage of the authoritarian regime entitled Estado Novo. Using as sources the newspapers, magazines and official documents, I pretend to problematize important aspects of the reorganization of the sports field in that period since the formation of the Conselho Regional dos Desportos directly linked to the interior secretary of Paraíba state associated to the entry of new political forces in the new federation, that provoked four collective resignations and two interventions throughout its existence, as well as the end of the more traditional clubs that had already participated in the previous Leagues. Issues such as the professionalization of players, the pluralization of journalistic discourse and the formation of clubs linked to factories in this period will also be approached in an attempt to understand the changes and permanences that accompanied the real applicability of the mentioned decree. This time it will be possible to analyze the scope of a national project for sports against the possible social plots that surrounded the backstage of sports in Paraíba.